Susceptibility of Clinical Moraxella catarrhalis Isolates in British Columbia to Six Empirically Prescribed Antibiotic Agents - Tamara Bandet; Sue Whitehead; Edith Blondel-Hill; Ken Wagner; Naowarat Cheeptham (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Moraxella catarrhalis is a commensal organism of the respiratory tract that has emerged as an important pathogen for a variety of upper and lower respiratory tract infections including otitis media and acute exacerbations of chronic bronchitis. Susceptibility testing of M catarrhalis is not routinely performed in most diagnostic laboratories; rather, a comment predicting susceptibility based on the literature is attached to the report. The most recent Canadian report on M catarrhalis antimicrobial susceptibility was published in 2003; therefore, a new study at this time was of interest and importance.